Comparative characteristics of power delivery and temperature between conventional and hybrid energy storage systems in UAVs - Phumma Prasophchok; Saikong Waiard (E3S Web of Conferences)
This research endeavors to present an analysis the characteristics of the power delivery and temperature between conventional energy storage systems (CESS) and hybrid energy storage systems (HESS) to aid in the development of advanced energy storage solutions for Unmanned Aerial Vehicles (UAVs). The results demonstrate that the HESS allows batteries to achieve one additional discharge cycle compared to CESS. Additionally, HESS reduces the initial current response and power delivery by 30W, enabling greater energy consumption efficiency. The average surface temperature differential between the two systems is 1.2°C and the average peak differential is 1.6°C, as the HESS exhibits a slower temperature rise during discharge two cycle to end, due to the initial assistance provided by the supercapacitor and maintain smooth surface peak temperature. The findings highlight the potential for HESS to enhance UAV performance, indicating the need for longer experiment durations, stable room temperatures, and consideration of the mission profile for more accurate data.